Obesity is associated with severe disease and mortality in patients with coronavirus disease 2019 (COVID-19): a meta-analysis - Zixin Cai; Yan Yang; Jingjing Zhang (BMC, 2021)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic has led to global research to predict those who are at greatest risk of developing severe disease and mortality. The aim of this meta-analysis was to determine the associations between obesity and the severity of and mortality due to COVID-19. Methods We searched the PubMed, EMBASE, Cochrane Library and Web of Science databases for studies evaluating the associations of obesity with COVID-19. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using random- or fixed-effects models. Meta-regression analyses were conducted to estimate regression coefficients. Results Forty-six studies involving 625,153 patients were included. Compared with nonobese patients, obese patients had a significantly increased risk of infection. (OR 2.73, 95% CI 1.53-4.87; I 2  = 96.8%), hospitalization (OR 1.72, 95% CI 1.55-1.92; I 2  = 47.4%), clinically severe disease (OR 3.81, 95% CI 1.97-7.35; I 2  = 57.4%), mechanical ventilation (OR 1.66, 95% CI 1.42-1.94; I 2  = 41.3%), intensive care unit (ICU) admission (OR 2.25, 95% CI 1.55-3.27; I 2  = 71.5%), and mortality (OR 1.61, 95% CI 1.29-2.01; I 2  = 83.1%). Conclusion Patients with obesity may have a greater risk of infection, hospitalization, clinically severe disease, mechanical ventilation, ICU admission, and mortality due to COVID-19. Therefore, it is important to increase awareness of these associations with obesity in COVID-19 patients.